In-process surface roughness recognition (ipsrr) system using acoustic emission (ae), part II - Ngu, S.H (Universiti Malaysia Sarawak, UNIMAS, 2004)
Ramp-up is a most important step in the implementation of manufacturing systems, and is even more significant in re configurable manufacturing systems. For a successful reduction in ramp-up time, it is essential to analyze and monitor both the overall manufacturing system and the individual machine tool or processes that comprise the system. Towards the whole project, we have to deal with the issue of monitoring surface roughness using acoustic emission to enable faulty conditions related with surface roughness to be recognized during the process before the quality of end product out of specification.